miRNA and antisense oligonucleotide-based α-synuclein targeting as disease-modifying therapeutics in Parkinson’s disease - Suvarna, Vasanti; Deshmukh, Kajal; Murahari, Manikanta (Frontiers in Pharmacology, 2022)
α-synuclein is the synaptic protein majorly involved in neuronal dysfunction and death and it is well known for the last two decades as a hallmark of Parkinson's disease. Alpha-synuclein is involved in neurodegeneration mediated through various neurotoxic pathways, majorly including autophagy or lysosomal dysregulation, mitochondrial disruption, synaptic dysfunction, and oxidative stress. Moreover, the alpha-synuclein aggregation has been associated with the development of several neurodegenerative conditions such as various forms of Parkinson's disease. The recent discovery in oligonucleotide chemistry has developed potential alpha-synuclein targeting molecules for the treatment of neurodegenerative diseases. The present review article focuses on recent advances in the applications of oligonucleotides acting via alpha-synuclein targeting mechanisms and their implication in combating Parkinson’s disease. Moreover, the article emphasizes the potential of miRNAs, and antisense oligonucleotides and the challenges associated with their use in the therapeutical management of Parkinson’s disease.